The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fphys.2022.929094
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNAs in the body wall of the sea cucumber Apostichopus japonicus under heat stress

Abstract: MicroRNAs, as one of the post-transcriptional regulation of genes, play an important role in the development process, cell differentiation and immune defense. The sea cucumber Apostichopus japonicus is an important cold-water species, known for its excellent nutritional and economic value, which usually encounters heat stress that affects its growth and leads to significant economic losses. However, there are few studies about the effect of miRNAs on heat stress in sea cucumbers. In this study, high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(46 reference statements)
2
1
0
Order By: Relevance
“…The rapid and persistent response of hsp70 indicates its critical role in the heat stress response of A. japonicus (Xu et al, 2015;Xu et al, 2016). The up-regulated expression of hsp70 in sea cucumbers under heat stress has also been detected in our previous study (Chang et al, 2022). Additionally, clca1 was found to be a key gene in IL-13 (Proinflammatory interleukin-13) dependent mucosal metaplasia (Alevy et al, 2012).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The rapid and persistent response of hsp70 indicates its critical role in the heat stress response of A. japonicus (Xu et al, 2015;Xu et al, 2016). The up-regulated expression of hsp70 in sea cucumbers under heat stress has also been detected in our previous study (Chang et al, 2022). Additionally, clca1 was found to be a key gene in IL-13 (Proinflammatory interleukin-13) dependent mucosal metaplasia (Alevy et al, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…Chen (2020) also revealed that DEGs in the intestine were significantly enriched in immune-related GO terms after heat stress of A. japonicus, such as toll-like receptor 3, carboxyterminal kinesin 2-like, and complement component C3. Studies have also shown that A. japonicus can respond to heat stress by regulating the expression of immune-related genes with some noncoding RNAs such as miRNA, circRNA and lncRNA (Huo et al, 2020;Huo et al, 2021;Chang et al, 2022). In the present study, the down-regulated DEGs were significantly enriched in immunerelated pathways such as notch signaling pathway, ubiquitin mediated proteolysis, and MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 57%
“…Splicing factor proline protein can regulate miRNA silencing on specific binding sites and globally impact miRNA-dependent gene expression programs [ 74 ]. Many studies have also reported that miRNAs can provide reversible gene silencing mechanisms in aestivation and hibernation and are involved in cellular adaptation to specific demands under stressful conditions [ 75 , 76 ]. In recent years, epigenetic factors have been thought to overwhelm gene expression and corresponding protein products.…”
Section: Perspectivementioning
confidence: 99%